Encephalitis secondary to nitrous oxide and vitamin B12 deficiency. Issue 12 (2nd December 2019) - Hughes, Gareth; Moran, Ed; Dedicoat, Martin J
Abstract : A 27-year-old woman presented with confusion, agitation and fever. Having initially been treated as an infective encephalitis case her initial and subsequent lumbar punctures revealed cerebrospinal fluid with a worsening pleocytosis and elevated protein. It was initially felt she had been suffering from tuberculous meningitis and started on treatment it later became apparent that she had a severe vitamin B12 deficiency related to recreational nitrous oxide use. She also was noted to have a peripheral neuropathy. After replacing her vitamin B12 and later stopping her tuberculous medication once cultures were negative her cognition and peripheral neuropathy continued to improve.